2016
DOI: 10.1590/s0100-83582016340400019
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Optimum Herbicide Mixtures to Manage and Avoid Fenoxaprop-p-Ethyl Resistant Phalaris minor in Wheat

Abstract: -Use of herbicide mixtures has been advocated as most effective strategy for avoidance and management of herbicide resistant weeds. Effect of twelve selected treatments of four herbicides (clodinafop-propargil, metribuzin, pinoxaden and sulfosulfuron) two-way mixtures at different doses was investigated against fenoxaprop-p-ethyl resistant and susceptible populations of P. minor grown along the wheat plants. In repeated experiment, herbicides mixtures were applied at 3 to 4 leaf stage of P. minor under greenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…In Pakistan, it occupies the first position among cereal crops (Noorka and Tabasum, 2013). The average yield of wheat crops does not exceed 30 to 35 percent of its potential yield in the country (Abbas et al, 2016). Thus, a yield gap exists between potential and actual yield that needs to be abridged through proper management practices (Noor, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, it occupies the first position among cereal crops (Noorka and Tabasum, 2013). The average yield of wheat crops does not exceed 30 to 35 percent of its potential yield in the country (Abbas et al, 2016). Thus, a yield gap exists between potential and actual yield that needs to be abridged through proper management practices (Noor, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Na cultura do trigo, mistura de herbicidas inibidores do Fotossistema II + inibidores da ACCase, não interfere na produtividade. No entanto, a mistura de inibidores da ALS + inibidores da ACCase reduz o crescimento e a produtividade (ABBAS et al, 2016).…”
Section: Resultsunclassified
“…The results showed that, while sulfosulfuron + clodinafop-propargyl at a 100% dose had phytotoxic effects on wheat, clodinafop-propargyl + metribuzin, pinoxaden + sulfosulfuron, and pinoxaden + metribuzin mixtures at a 100% dose did not harm the crop. However, all mixtures mentioned above successfully controlled herbicideresistant P. minor at a 75% dose without any phytotoxic effects on wheat [111,112].…”
Section: Management Of Herbicide Resistance In Phalaris Sppmentioning
confidence: 98%